HUBUNGAN KEPATUHAN DIET RENDAH PURIN DENGAN ASAM URAT DI PUSKESMAS WARA KOTA PALOPO TAHUN 2016 - Ampin Maja, Abdullah Sappe (Voice of Midwifery, 2017)
The research of this research to analysis dietary compliance of low purine diet in uric acid patients in Wara Health Clinic Year 2016. Type of this research that was used cross sectional approach and use a sampling technique was purposive sampling. The sample of the research was a portion of gout patients enrolled in Wara Health Clinic that fulfilled the inclusion criteria were 42 people.Based on the analysis by using statistical test Fisher's exact test, the value p = 0468 (p> 0.05%), it can be concluded that the hypothesis "there is no correlation between dietary compliance low purine with uric acid in Puskesmas Wara Palopo".Based on the result of research purpose recommendations were provide clearly information about the low purine diet and provide support in the form of motivation for pay attention of type food consumed so as to prevent the increasing of uric acid. Keywords : Compliance, Diet Low Purin, Uric Acid